P762 Population Pharmacokinetic Model of Intravenous Infliximab in Korean Patients with Crohn's Disease. (30th January 2023) - Seo, J; Lee, M H; Hong, H; Oh, E H; Hwang, S W; Park, S H; Yang, D H; Byeon, J S; Myung, S J; Yang, S K; Bae, K S; Ye, B D
Abstract: Background: Infliximab (IFX), a monoclonal antibody approved for treating Crohn's disease (CD), is known to show differing drug clearances in patients according to several clinical factors. However, information on the population pharmacokinetics (PKs) of intravenous (IV) IFX is lacking for Korean patients with CD. Therefore, in this study, we aimed to establish a PK model of IV IFX for this population. Methods: We retrospectively analyzed data of CD patients treated with IV IFX at Asan Medical Center, a tertiary university hospital, from April 2019 to March 2022. Serum trough IFX concentration, clinical laboratory values, Crohn's disease activity index, and demographic data were collected. NONMEM ® version 7.5 was used for nonlinear mixed effects modeling. Results: Of the one hundred patients included for analysis in this study, 72 were male (72.0%) (Table 1). No patient had detectable antibodies to IFX. [SJ1] A total of 823 serum IFX concentration data were collected and analyzed for fitting according to the minimization of objective function value and weighted residuals. As a result, a one-compartment population PK model with first-order elimination best described the serum trough IFX concentration measurements. Population PK estimates were 0.012 L/h for clearance (CL) (95% confidence interval: 0.012–0.013) and 6.301 L for the volume of distribution (V) (95% confidence interval: 5.932–6.671) (Table 2). Covariate analysis showed that CL and V increased as body weight increased. CL was higher in patients with low serum albumin, high serum C-reactive protein, and older age, with differing coefficients for each covariate (Figure 1). The final covariate model predicted the observed concentration-time profiles of IFX reasonably well (Figure 2). Conclusion: We established a population PK model of IV IFX for CD patients in Korea. The final covariate model showed that the CL of IFX was affected by serum albumin and C-reactive protein levels, in addition to body weight and age.